New correlation to predict the onset of flow instability (OFI) heat flux of one-side heated hypervapotron channel for fusion reactor application. (22nd September 2021) - Lim, Ji Hwan; Lee, Su Won; Park, Minkyu; Oh, Hoongyo; Hwang, Donkoan; Kim, Moo Hwan; Jo, HangJin
Abstract: In this study, the onset of flow instability (OFI) of the hypervapotron channel was experimentally explored under one-side high heat load conditions. The OFI was detected based on the heat flux ( q ″ ) where the standard deviation of the inlet pressure rapidly increased. Moreover, the effect of the system parameters was analyzed, showing that the OFI q ″ increased as the inset subcooling and mass flow rate increased. The reason is the high subcooling and flow rate that rapidly condense the vapor, which is the leading cause of OFI. Unfortunately, because most of the OFI correlations in previous studies were developed based on micro-channels, these correlations could not predict the hypervapotron OFI q ″ properly under one-side high heat load conditions. Finally, the authors found that the Reynolds number and Jakob number were inversely proportional to the ratio of the OFI heat flux ( q O F I ″ ) and saturation heat flux ( q s a t ″ ). Furthermore, a new correlation was developed using a PYTHON code and an artificial intelligence technique (mean absolute error rate = 12.89%, root mean square error rate = 14.81%).